2020
DOI: 10.1075/jlp.19028.vat
|View full text |Cite
|
Sign up to set email alerts
|

EU nationals in the UK after BREXIT

Abstract: The United Kingdom’s decision to leave the European Union has triggered a variety of forms of political engagement among EU nationals living in the UK. Our research, carried out in the North West of England, an area that has received little attention so far, demonstrates that the result of the 2016 Referendum sparked a new awareness of public discourse, has led to the emergence of new political and discursive attitudes and strategies, as well as persu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Our interest is to identify the shifting characteristics of diaspora communities, with a specific focus on Romanian diasporas. Recognising the contribution that previous studies made to the current topic (Dolea, 2018(Dolea, , 2020(Dolea, , 2022Trandafoiu, 2013;Vathi and Trandafoiu, 2020), our research identifies three forms of engagement in the case of Romanian diaspora diplomacy: mediation, representation and advocacy. While previous studies have identified a rising political awareness and visibility in the host societies of Romanian diasporic communities, our research develops this particular dimension within the broader framework of diaspora diplomacy.…”
Section: Diaspora Diplomacy and Modes Of Engagementmentioning
confidence: 85%
See 1 more Smart Citation
“…Our interest is to identify the shifting characteristics of diaspora communities, with a specific focus on Romanian diasporas. Recognising the contribution that previous studies made to the current topic (Dolea, 2018(Dolea, , 2020(Dolea, , 2022Trandafoiu, 2013;Vathi and Trandafoiu, 2020), our research identifies three forms of engagement in the case of Romanian diaspora diplomacy: mediation, representation and advocacy. While previous studies have identified a rising political awareness and visibility in the host societies of Romanian diasporic communities, our research develops this particular dimension within the broader framework of diaspora diplomacy.…”
Section: Diaspora Diplomacy and Modes Of Engagementmentioning
confidence: 85%
“…Since 2013, however, there have been important shifts in the dynamics of Romanian diaspora in the UK Recent studies (Vathi and Trandafoiu, 2020;Dolea, 2018Dolea, , 2022 mention the increasing civic engagement and political activity. Building public legitimacy is an important agenda which any diaspora attempts to achieve; however, the Romanian diaspora in the UK has a distinct mode of expression, and that is through its network type of configuration, with extended bridging links which reflect a high relational capacity.…”
Section: Diaspora Diplomacymentioning
confidence: 99%